Exome Sequencing Reveals Signal Transduction Genes Involved in Impulse Control Disorders in Parkinson's Disease - Prud'hon, Sabine; Bekadar, Samir; Rastetter, Agnès; Guégan, Justine; Cormier-Dequaire, Florence; Lacomblez, Lucette; Mangone, Graziella; You, Hana; Daniau, Mailys; Marie, Yannick; Bertrand, Hélène; Lesage, Suzanne; et al. (Frontiers in Neurology, 2020)
Introduction: Impulse control disorders (ICDs) frequently complicate dopamine agonist (DA) therapy in Parkinson's disease (PD). There is growing evidence of a high heritability for ICDs in the general population and in PD. Variants on genes belonging to the reward pathway have been shown to account for part of this heritability. We aimed to identify new pathways associated with ICDs in PD. Methods: Thirty-six Parkinsonian patients on DA therapy with (n = 18) and without ICDs (n = 18) matched on age at PD's onset, and gender was selected to represent the most extreme phenotypes of their category. Exome sequencing was performed, and variants with a strong functional impact in brain-expressed genes were selected. Allele frequencies and their distribution in genes and pathways were analyzed with single variant and SKAT-O tests. The 10 most associated variants, genes, and pathways were retained for replication in the Parkinson's progression markers initiative (PPMI) cohort. Results: None of markers tested passed the significance threshold adjusted for multiple comparisons. However, the “Adenylate cyclase activating” pathway, one of the top associated pathways in the discovery data set (p = 1.6 × 10−3) was replicated in the PPMI cohort and was significantly associated with ICDs in a post hoc pooled analysis (combined p-value 3.3 × 10−5). Two of the 10 most associated variants belonged to genes implicated in cAMP and ERK signaling (rs34193571 in RasGRF2, p = 5 × 10−4; rs1877652 in PDE2A, p = 8 × 10−4) although non-significant after Bonferroni correction. Conclusion: Our results suggest that genes implicated in the signaling pathways linked to G protein-coupled receptors participate to genetic susceptibility to ICDs in PD.